Note on the taxonomy of the Microtus (Iberomys) (Arvicolinae, Rodentia) from the Late Pleistocene of Gruta do Caldeirão (Tomar, Portugal) and paleoclimatic interpretation of the rodent assemblage - López-García, Juan Manuel (2021)
Gruta do Caldeirão is an archaeological cave site located in Tomar (Portugal, western Iberian Peninsula), which contains an important Late Pleistocene sequence from Middle Paleolithic (Mousterian) to Upper Paleolithic (Solutrean-Magdalenian), including lithic tools, human remains, and other large- and small-vertebrate remains. Our revision and interpretation of the rodent assemblage previously published in the 1990s leads to three important conclusions: 1) the only species of the subgenus Iberomys present in the sequence is the current endemic Iberian vole species Microtus (Iberomys) cabrerae (Cabrera’s vole); 2) the rodent assemblage is dominated throughout by open-forest species, such as the long-tailed field mouse (Apodemus sylvaticus), and species associated with open-humid areas such as the Mediterranean and Lusitanian pine voles (Microtus (Terricola) spp.), with the notable presence of an extinct hamster (Allocricetus bursae) in layer K, and three vole species not currently found in the vicinity of the cave (Microtus arvalis [the common vole], M. Agrestis [the field vole], and Chionomys nivalis [the European snow vole]) also in the assemblage; 3) the bioclimatic model, which is used to reconstruct climatic parameters on the basis of the rodent association, corroborates the proposal that the Solutrean occupation from layers H to Fa took place during a cold period equated to the Last Glacial Maximum (LGM), as indicated by the available radiocarbon dates and supported by the magnetic susceptibility data.